IN VITRO AND IN SILICO ANTIMICROBIAL STUDY OF STANNANE OF PYRIDOXAL 5-PHOSPHATE - Aniyery, Rohit Babu; Gupta, Anita; Singh, Prashant; ., Sanju (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The main objective of this research work is to synthesize a novel stannane of pyridoxal 5-phosphateand to study its antibacterial property. Methods: Conventional method was used to synthesize the stannane of pyridoxal 5-phosphateand its characterization was carried using UV-visible and 1H NMR. The antibacterial study was carried against, Staphylococcus aureus (gram positive) and Escherichia coli 1610(gram negative) using well diffusion method. In silico antimicrobial was carried out using computational software iGemDock v2.1 tool.(Graphical Drug Design system for Docking, Screening, and Post-analysis), computational docking was carried out using different PDB (Protein Data Bank) files (2I42, 3EOO, 3D2U and 3D2Y). The structure was optimized prior docking using Gaussian software, and the method followed was Energy (Ground state) Hartree-Fork. Results: It was observed that the stannane of pyridoxal 5-phosphateinhibited bacterial growth of Staphylococcus aureus (gram positive) and Escherichia coli 1610 (gram negative) in vitro antibacterial study. The complex has shown good docking results on almost all the receptors, with interaction supporting the fitting of the drug to the target molecules. The novel complex has shown good antibacterial activity (theoretically) in insilico studies. It was found to having a good potency to efficiently inhibit the microbes Burkholderia pseudomallei, Human cytomegalovirus, Yersinia enterocolitica and Escherichia coli, based on the interaction profile. The synthesized stannane was found to be effective in halting the undesirable effects of selected PDB files. Conclusion: On the basis of the above findings in the present research work, the novel complex was found to be a good antimicrobial agent and our future studies will aim design of novel selective and potent inhibitors. Further in vitro studies of this compound against these bacteria will lead to a new pathway to a novel antibacterial drug discovery.